2018
DOI: 10.1590/s1980-220x2017029703372
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with non-adherence to outpatient follow-up of neonatal intensive care discharge

Abstract: Objective: To analyze the factors associated with non-adherence to the outpatient follow-up of infants discharged from the Neonatal Intensive Care Unit. Method: A cross-sectional study that included 596 children who were discharged between October 1, 2014 and September 30, 2015 and who were referred to outpatient follow-up. The data were collected by evaluating the discharge report and attendance to the consultations. Results: Of the 596 children referred for follow-up, 118 (19.80%) did not attend any outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…The Incentive Support subscale obtained a good average, which was also found in other similar studies 21,22 . The answers given to "It encouraged me to ask questions about my child" and "It allowed me to know if I was doing something good to help my child" highlighted the need for establishing continuing education so that the team understands the need to encourage family members to help create a link in the healthy growth and development of the newborn 16,[29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…The Incentive Support subscale obtained a good average, which was also found in other similar studies 21,22 . The answers given to "It encouraged me to ask questions about my child" and "It allowed me to know if I was doing something good to help my child" highlighted the need for establishing continuing education so that the team understands the need to encourage family members to help create a link in the healthy growth and development of the newborn 16,[29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Among related factors, we can highlight: distance between residence and service, preference for a specific health professional, illness in the family, change of address, unfavorable socioeconomic and cultural characteristics of families, and having other children (7)(8)(9)(10) . A Brazilian study, conducted in the state of Minas Gerais, showed that 19.8% of children who were hospitalized at a NICU with referral to the outpatient follow-up did not attend any appointment in the first 12 months of life (11) . Aspects of the discontinuity of outpatient follow-up of children at risk have been little explored in the national context, especially the factors that can contribute to its occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that children at risk who were hospitalized in NICU present the highest risk of changes in growth and development as well as of occurrence of morbidities in the medium and longterm. This risk is aggravated when these children do not get a qualified assistance that encompass the peculiarities of their needs (2,11) . We considered, therefore, the need to understand the factors associated with the discontinuance of outpatient follow-up and the possible interferences in the families' decision regarding the use of health care services to children who were hospitalized at a NICU.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neste sentido, prevalece o consenso de que os recém-nascidos (RN) egressos de Unidades de Terapia Intensiva Neonatal (UTIN) se mostram mais suscetíveis a taxas elevadas de morbimortalidade depois da alta hospitalar, dada a sua fragilidade fisiológica decorrente das condições da gestação, nascimento e o tempo de internação (Shoo et al, 2020). Ademais, estes neonatos ficam expostos a acometimentos neurológicos, respiratórios, cardíacos, dentre outros, com desdobramentos prejudiciais ao seu desenvolvimento (Freire et al, 2019).…”
Section: Introductionunclassified